Estimation of Concentration of Selected Heavy Metals in Muscle, Liver and Bones of Pigs : 10.5958/2581-6616.2020.00022.5 - Thomas, R.; Singha, S.; Saikia, M.; Kalita, R.; Baruah , Z.; Saharia, N. (Journal of Meat Science, 2020)
Pork is a very rich and convenient source of nutrients including microelements. Evaluation and monitoring of heavy metal concentration in pork is very much important from the consumer safety point. In the present study, concentration of selected heavy metals viz., Tin (Sn), Lead (Pb), Cadmium (Cd), Arsenic (As) and Mercury (Hg) in pig muscle, liver and bones collected from different parts of Kamrup District, Assam were evaluated using atomic absorption spectroscopy. The results indicated that the concentration of studied metals was not exceeding the maximum permissible limit (MRL) recommended by FSSAI. The results also indicated that the concentration of Sn was significantly higher in bones (14.52±2.41ppm) compared to muscle tissues (9.53±2.49 ppm). The concentration of Sn, Pb, Cd, As and Hg in the muscle tissue was in the range of 0.00-21.61 (ppm), 0.01-0.07 (ppm), 0.00-0.005 (ppm), 0.00-1.75 (ppb) and 0.00-0.40 (ppb), respectively. The mean concentration of Cd and As in muscle tissue (0.001±0.001ppm and 0.85±0.28ppb, respectively) was comparatively lower than that in the liver (0.01± 0.01ppm and 1.13±0.81ppb, respectively). The results also indicated that the level of Pb was more in muscle tissues compared to liver. In liver, the range of heavy metals were 0.00-0.04 (ppm), 0.00-0.03 (ppm) and 0.00- 2.31 (ppb) for Pb, Cd and As, respectively.